Peran Bimbingan Perkawinan Kantor Urusan Agama dalam Mencegah Perceraian dan Membangun Kebahagiaan Keluarga - Asa'diah, Alfiah; Muhsan Syarifuddin (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2025)
This research aims to determine the essence of the marriage guidance program carried out by the KUA Sumbersari Jember District in order to reduce the divorce rate that occurs in Jember. Looking at the national divorce rate, Jember Regency, especially Sumbersari District, has the highest divorce rate in East Java. As shown in 2022 data which reached 516,334 cases. In order to reduce divorce in Indonesia, the Ministry of Religion launched a marriage guidance program. As a prelude to marriage, prospective brides and grooms receive advice from a marriage guidance program. The aim of the marriage guidance program is to provide understanding to couples who are getting married regarding knowledge related to the household. The approach in this research uses a case study method and a qualitative approach with extension workers from the KUA Sumbersari District as informants in this research. The research findings show that: (1) The Sumbersari District KUA marriage guidance program provides materials to couples who want to get married. (2) There are several factors behind divorce and the impact left behind by a divorce. (3) Efforts to prevent divorce that can be carried out by the KUA are by providing marriage guidance and giving advice to prospective brides and grooms. Meanwhile, efforts that couples can make are to understand and understand each other and carry out their respective rights and responsibilities.